Notice of the outfort on Barry Hill, Forfarshire recently removed (Proceedings of the Society of Antiquaries of Scotland, 1856)
A discussion of an outfort on Barry Hill that was destroyed the previous year. The dimensions of the fort and the materials used suggest that it was a place people intended to retreat for safety. The author also mentions some of the finds that were discovered during the outfort's excavation.